Pelatihan pembuatan pupuk organik bokashi - Mithen Lullulangi; Onesimus Sampebua (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Farmers who are members of the Sariayo Farmer Group, for the most part, traditional farmers who work on agricultural land such as rice fields and hereditary gardens inherited from their parents and or ancestors. In processing these agricultural lands in the modern era, they are already familiar with fertilizers and medicines such as urea, ZA, KCL, Phosphorus, as well as herbicides and insecticides. These chemical fertilizers and medicines are introduced by field extension agents (PPL) who interact with them at any time in the field, in order to increase agricultural yields for their daily needs. The current problems are: 1). The level of fertility of their agricultural land is decreasing. 2) Farming carried out still relies on chemical fertilizers as the main fertilizer, without knowing the long-term effects of the use of chemical fertilizers that can result in environmental pollution. 3) They do not know yet the manufacture and use of alternative fertilizers, namely organic fertilizers which are more economical and environmentally friendly. The solution offered in this training is to provide counseling and training to farmers about making organic fertilizer bokashi.The outputs of this activity are: 1) Twenty (20) partner farmers have knowledge and skills about making bokashi organic fertilizer 2) Partner knowledge can continue and develop and can be passed on to fellow farmers in their respective environments. The target audience (partners) of this activity are farmers who are members of the Sariayo Farmer Group in West Balla Village, Balla District, Mamasa Regency. The results of this program are expected to improve partners' knowledge and skills